Design a T2DM-meal plan by enhancing current practice using linear programming / Hanan Abdul Karim, Noraini Noordin and Noor Zaini Yasok - Abdul Karim, Hanan; Noordin, Noraini; Yasok, Noor Zaini (Universiti Teknologi MARA, Perlis, 2015)
Changing lifestyles, ignorance of nutritional knowledge and low health consciousness among Malaysians have promoted the alarming increase of diabetes cases today. Currently, an optimal palatable meal for T2DM-affected individuals is not achievable because dieticians have to perform tedious manual calculations; differentiated views on meal plan; and limited consultation time. In addition, none of the few researches on T2DM-meal planning have applied exchange lists currently practiced by dietitians. To provide a mathematical solution to the problem, this research has used linear programming to develop a meal plan as it has the ability to find the best optimal solution when all the constraints are satisfied, and also as an alternative to the current practices. A Malaysian food exchange list for T2DM-affected individuals based on available information in the Atlas was created for this purpose. Adapting the current standard dietitian practice and available guidelines has also made design of T2DM-meals more direct and logical with the production of two different models, Exchange Planner and Meal Planner. These models can translate dietary recommendations into actual food exchange plans as well as suggest the amount of food intakes for each meal or snack. In conclusion, the resultant meal plans have successfully minimized energy intakes and satisfied specified restrictions which may simultaneously improve glycaemic control and lessen risk of complications for individuals with T2DM.